Optical Limiting and Dynamical Two-Photon Absorption for Femtosecond Laser Pulses in BDBAS (Journal of Atomic and Molecular Sciences, 2014)
By numerically solving the Maxwell-Bloch equations using an iterativepredictor-corrector finite-difference time-domain (FDTD) technique, the optical limiting(OL) and two-photon absorption (TPA) properties for femtosecond laser pulses ina strong TPA organic molecular (4,4'-bis (di-n-butylamino) stilbene (BDBAS))mediumare studied. The medium has obvious OL behavior in a certain intensity region whichis dependent on the propagation distance, sample concentration, input pulse widthand effect of optical ionization. Moreover, dynamical TPA cross sections are obtained,showing an increasing trend with the broadening of the pulse width and the propagationdistance in the femtosecond time domain.